2003
DOI: 10.1542/peds.112.4.e269
|View full text |Cite
|
Sign up to set email alerts
|

Parental Knowledge, Attitudes, and Practices Associated With Not Receiving Hepatitis A Vaccine in a Demonstration Project in Butte County, California

Abstract: ABSTRACT. Objective. To determine hepatitis A vaccination coverage and factors associated with not receiving hepatitis A vaccine among children.Methods. A random cluster sample survey was conducted of parents of children who attended kindergarten in Butte County, California, in 2000. Because of a history of recurrent epidemics, an aggressive hepatitis A vaccination program was ongoing during the time this study was conducted. Receipt of 1 or 2 doses of hepatitis A vaccine was studied.Results. Of 896 surveys se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 20 publications
2
28
1
2
Order By: Relevance
“…Bardenheier et al, 2003). The finding that the availability of a person to assist with taking the child for immunization increases the odds of obtaining BCG vaccine is in consonance with evidence from other cultural settings (e.g.…”
Section: Discussionsupporting
confidence: 68%
“…Bardenheier et al, 2003). The finding that the availability of a person to assist with taking the child for immunization increases the odds of obtaining BCG vaccine is in consonance with evidence from other cultural settings (e.g.…”
Section: Discussionsupporting
confidence: 68%
“…This has resulted in increased negligence about vaccination, and the balance has shifted from emphasizing the true benefits of vaccination to increased suspicion of adverse effects of vaccination. Parents who are reluctant to have their children or themselves vaccinated often consider vaccine- preventable diseases as either rare or mild, or irrelevant to their own children [23,25,29,30]. Respondents to the EVM survey were more likely to get vaccinated for travel to a foreign country than for any other reason [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers cite lack of knowledge about HPV prevention and transmission as a major barrier to vaccine compliance [7,8]. Others have shown that knowledge can be an important predictor of vaccine behavior [911]. …”
Section: Introductionmentioning
confidence: 99%